Linguistic Errors in Speech Production: An Analysis of Slips of the Tongue among Malay ESL Learners in Universiti Islam Selangor (UIS) - Mahdun, Mahanum; Afifah , Wan Nazhryna (Modality Journal: International Journal of Linguistics and Literature, 2025)
Slips of the tongue (SOT) are unintentional speech errors that reflect the cognitive and linguistic processes underlying second language production. This study examined the occurrence, types, and contributing factors of SOT among Malay ESL learners at Universiti Islam Selangor (UIS) using a mixed-methods design. Findings showed that 64.7% of participants produced at least one SOT, with additions being the most frequent, followed by anticipation, reversal, and substitution. Affective factors, including anxiety, shyness, and overconfidence, were identified as key triggers, disrupting both language processing and oral performance. These results underscore the need for targeted pedagogical interventions to reduce speech errors and enhance learners’ fluency. The study contributes to a deeper understanding of second language speech production and offers practical implications for ESL educators in designing strategies to improve oral competence and confidence.